The Effectiveness of Corporate Governance on Earnings Management in Companies Listed on the Main Board of Singapore Exchange (SGX) - Ngete, Zipora Adoyo (2013)
Firms that are well governed have been found to have lower earnings manipulation. This paper therefore aims to examine the effectiveness of corporate governance mechanisms on reducing earnings management among 326 listed companies on the Singapore Exchange (SGX) main board between the years 2010 and 2011. We first ran the descriptive statistics for both the dependent and independent variables to determine their overall composition through observing their means. We then used logistic regression to test whether the corporate governance characteristics of board independence, CEO duality and the sizes of audit, remuneration and nomination committees have an effect on the discretionary accruals level of the sampled Singapore firms. Our results were contrary to what we expected as shown from prior studies on this topic in the sense that they showed how discretionary accruals is only significantly related to remuneration committee size but not significantly related with all the other corporate governance variables tested. These results show how earnings management in Singapore firms may not necessarily be influenced by a firm’s board characteristics and therefore we recommend that other firm characteristics or control variables should be used, to see whether they affect earnings management in Singapore firms, in addition to the governance characteristics tested in this study.